Discovery of gamma-ray emission from the extragalactic pulsar wind nebula N 157B with H.E.S.S. - Abramowski, A.; Acero, Fabio; Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; Balenderan, S.; Balzer, Arnim; Barnacka, A.; Becherini, Y.; Becker, J.; Bernloehr, K.; Birsin, E.; et al. (Astronomy & Astrophysics, 2012)
We present the significant detection of the first extragalactic pulsar wind nebula (PWN) detected in gamma rays, N- 157B, located in the large Magellanic Cloud (LMC). Pulsars with high spin-down luminosity are found to power energised nebulae that emit gamma rays up to energies of several tens of TeV. N- 157B is associated with PSR- J0537-6910, which is the pulsar with the highest known spin-down luminosity. The High Energy Stereoscopic System telescope array observed this nebula on a yearly basis from 2004 to 2009 with a dead-time corrected exposure of 46- h. The gamma-ray spectrum between 600- GeV and 12- TeV is well-described by a pure power-law with a photon index of 2.8 ± 0.2 ± 0.3 and a normalisation at 1- TeV of (8.2 ± 0.8 ± 2.5 ) × 10 cm - s - TeV . A leptonic multi-wavelength model shows that an energy of about 4 × 10 erg is stored in electrons and positrons. The apparent efficiency, which is the ratio of the TeV gamma-ray luminosity to the pulsar's spin-down luminosity, 0.08% ± 0.01%, is comparable to those of PWNe found in the Milky Way. The detection of a PWN at such a large distance is possible due to the pulsar's favourable spin-down luminosity and a bright infrared photon-field serving as an inverse-Compton-scattering target for accelerated leptons. By applying a calorimetric technique to these observations, the pulsar's birth period is estimated to be shorter than 10 ms. © ESO, 201
Keywords: Gamma rays: general; ISM: supernova remnants; Magellanic Clouds; Pulsars: individual: PSR J0537-6910